(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
Now a days we know that there is need to use renewable energy source . To use the renewable energy of sun there are many innovative devices deals with capturing maximum solar energy and convert it into useful energy through the use of solar panels . One particular device is couple with a to collect maximum energy of sun it is necessary that the position of solar plate is perpendicular to the sun.so to change position of plate continuous we used hydraulic system in which hydraulic cylinder is used with flow control valve